Acesso aberto à informação científica: estudo sobre sistemas de informação da Universidade Federal de Minas Gerais - Raisa Mendes Fernandes de Souza (2012)
The research proposes to characterize information systems at the Federal University of Minas Gerais, nature of academic and scientific, working with institutional production, investigating how and when they were created and how they are featured within the attributes of a digital repository access open to scientific information. Thus, we analyzed the perception of the actors responsible for its existence and maintenance within the context of Open Access to Scientific Information. For this, we need to map and describe the nature of information systems existing in the academic and scientific institutions, which have already been implemented, identify, based on the literature, a set of attributes that characterize an institutional repository of open access to scientific information, analyze the typology of systems found according to literature review; consult user segments UFMG about knowledge and use of these systems and finally diagnose the situation at the University for the possible implementation of an Institutional Repository. Were consulted teachers, students and employees responsible for the maintenance of information systems to analyze how these potential users utilize each system. Were also consulted their system managers to capture what is their understanding about the system that manages, the others existing in the university and about the Open Access Movement to scientific information. The results of questionnaires aimed at understanding how the community deals with the scientific open access, built locally, serving as a subsidy for a discussion of the factors that inhibit and encourage the implementation of an institutional repository at UFMG. It was concluded that a significant number of systems does not match the type of digital repository, resulting in the impossibility of their collections fit within an institutional repository, however, this does not block the UFMG develop, more efficiently, an RI. Generally, UFMG has sufficiently competent managers and responsible for managing a repository greater, as is the case of an RI, and also have appropriate technology. But, its necessary a policy of scientific consolidated, born in the sectors hierarchically superior, being passed on to the lower sectors to be able to articulate well the entire university community in support of a common cause. The study highlights the community UFMG and optimization of open access to publications of the University as the scope for possible future studies.